First- and Second-Order Sensitivities of Steady-State Solutions to Water Distribution Systems - Olivier Piller; Sylvan Elhay; Jochen W. Deuerlein; Angus R. Simpson (Engineering Proceedings)
First-order approximations have been used with some success for criticality analysis; sensitivity analysis of physical networks, such as water distribution systems; and uncertainty propagation of model parameters. Certain limitations have been reported regarding the accuracy of the results, particularly when non-linearity is dominant. In this paper, we show how to efficiently derive the first- and second-order sensitivities with respect to variation in their parameters. This makes it possible to improve the first-order estimate when necessary. The method is illustrated on a small example system.